Approaches on the influences of learning music in the development of the children of six years (2016)
The article proposes some reflections on the incidence of musical learning in the development of six-year-old children. It raises whether music education acts in its evolution and, in addition, presents different considerations about how it can influence development from an emotional point of view. , engine and language area. From October 2013 to May 2015, the rigorous study of scientific literature dedicated to the development of musical education in the psychological, cognitive and affective aspects of the development of the musical sense and language was carried out to carry out the research. These studies focused on different stages of the child, from fetal status to school age. Likewise, observations were made for six months in a primary school in Paris, France, in groups of six-year-old children, both in their music classes and in other subjects, in order to establish comparisons and deductions to take conduct such investigation. The author's professional experience in music education was also based.